Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1007/bf02055386
|View full text |Cite
|
Sign up to set email alerts
|

Lateral internal sphincterotomy for fissure-in-ano—Revisited

Abstract: This review supports the belief that LIS is a good operation for patients with chronic anal fissure and can successfully be performed under local anesthetic as an outpatient procedure with an acceptable complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 28 publications
1
35
0
7
Order By: Relevance
“…In our study in the surgical treatment group, 96 % of the patient showed complete healing of their fissure in 8 weeks. Hananal and Gordon [13] reported a healing rate of 84 % in 4 weeks raised to 94.4 % in 8 weeks. In our study ulcer healing at 8 weeks was significantly higher (p=0.004) in surgical treatment group (96.0 %) than in medical treatment group (76.0 %).…”
Section: Discussionmentioning
confidence: 98%
“…In our study in the surgical treatment group, 96 % of the patient showed complete healing of their fissure in 8 weeks. Hananal and Gordon [13] reported a healing rate of 84 % in 4 weeks raised to 94.4 % in 8 weeks. In our study ulcer healing at 8 weeks was significantly higher (p=0.004) in surgical treatment group (96.0 %) than in medical treatment group (76.0 %).…”
Section: Discussionmentioning
confidence: 98%
“…Patient not relieved of fissure symptom or recurrence was surgically treated using. 7,8 lateral internal sphincterotomy with sentinel tag excision.…”
Section: Methodsmentioning
confidence: 99%
“…6 manual anal dilatation or. 7,8,9 lateral internal sphincterotomy, effectively heal most fissures within a few weeks, but may result in permanently impaired anal continence. The present study assess the effectiveness and side effects of topical application of 2%.…”
Section: Introduction 123mentioning
confidence: 99%
“…Dados semelhantes foram relatados por GarciaAguilar et al 15 em série extensa de pacientes. Porém, outros autores apresentaram índices de incontinência menores em suas séries, gerando controvérsia sobre os resultados deste procedimento [15][16][17][18] . De qualquer forma, a lesão do esfíncter interno do ânus e, por vezes do esfíncter externo que ocorrem nesta operação favorecem o desencadeamento de incontinência fecal, principalmente em pacientes mais idosos ou com defeitos ocultos do aparelho esfincteriano, que ocorrem em mulheres com partos vaginais prévios 19,20 .…”
Section: Cirurgias Orificiaisunclassified